2021
DOI: 10.30632/pjv62n4-2021a4
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Sonic Log Generation With Machine Learning: A Contest Summary From Five Methods

Abstract: Compressional and shear sonic traveltime logs (DTC and DTS, respectively) are crucial for subsurface characterization and seismic-well tie. However, these two logs are often missing or incomplete in many oil and gas wells. Therefore, many petrophysical and geophysical workflows include sonic log synthetization or pseudo-log generation based on multivariate regression or rock physics relations. Started on March 1, 2020, and concluded on May 7, 2020, the SPWLA PDDA SIG hosted a contest aiming to predict the DTC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Quantification of electrical behavior in porous media has supported advancements in petroleum reservoir characterization 46 , 47 , CO 2 monitoring in carbon capture and storage 48 , hydrogeology 49 , mineral exploration 50 , and battery development 51 . In these composite systems, electrical conductivity measurements aid in inferring the composition of the material and its phase distributions.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of electrical behavior in porous media has supported advancements in petroleum reservoir characterization 46 , 47 , CO 2 monitoring in carbon capture and storage 48 , hydrogeology 49 , mineral exploration 50 , and battery development 51 . In these composite systems, electrical conductivity measurements aid in inferring the composition of the material and its phase distributions.…”
Section: Methodsmentioning
confidence: 99%
“…To perform more accurate reservoir characterization, many machine-learning methods have been previously proposed for lithology identification, depth matching, formation property estimation, and well-log correlation in carbonate and clastic reservoirs (Gashler, 2008;Bestagini et al, 2017;Sidahmed et al, 2017;Shashank and Mahapatra, 2018;Bennis and Torres-Verdín, 2019;Brazell et al, 2019;Liang et al, 2019;Shao et al, 2019;Yu et al, 2021). Compared to petrophysical model-based methods, e.g., Timur-Coats equation and Windland's equation (Leverett, 1941;Timur, 1968), machine-learning approaches obtain better results by fitting more complex relationships between well logs and formation properties.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al found that data cleaning and clustering were critical for improving the performance in all models. However, it was also found that it was necessary to adopt median filtering for input logs to alleviate the aliasing problem caused by data interpolation and eliminate outliers [15].…”
mentioning
confidence: 99%